UiTM Faculty of Pharmacy presents Pharmacare 2025 to promote health awareness and community engagement / Farhana Fakhira Ismail, Nur Sabiha Md Hussin and Gurmeet Kaur Surindar Singh - Ismail, Farhana Fakhira; Md Hussin, Nur Sabiha; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2025)
On January 11, 2025, the PharmaCare programme took place at UiTM, bringing together students, faculty members, and the public for a day of insightful talks, interactive activities, and health awareness initiatives. The event, organised as part of a Community Pharmacy (PHC670) and Know Your Medicine (UPH654) assessment, was a success in promoting knowledge and awareness of public health. Apart from the booths with several health-related topics, one of the major highlights was the blood donation drive. This initiative encouraged civic responsibility and helped raise awareness about the importance of blood donation.